MEMUDARNYA NILAI KEARIFAN LOKAL MASYARAKAT DALAM PENGELOLAAN SUMBER DAYA AIR - Deny Hidayati (Research Centre for Population, Indonesian Institute of Sciences, 2016)
Water is vital for human and thus it has to be made available for our life. Many communities in Indonesia, with their local knowledge, customs, and culture that are passed from generations, utilize water resources in their areas to meet daily needs. They manage the resources and live in harmony with the surrounding nature. The wisdom of community on water resource management, unfortunately, has experienced a shift. Water has then become an important issue that requires significant attention. This paper discusses shift in the value of local wisdom on water resources. Data and information in this paper is based on desk reviews from research/assessment results, books, documents and the author’s field experiences in implementing relevant researches. The discussion focuses on the waning of local knowledge and wisdom as social capital in the provision of community water supply and as a form of their protection against water resources, such as the erosion of togetherness and mutual cooperation among members of the community, change in the value of water from social good to commercialization, the waning of local and traditional institutions, and the community’s sense of belonging to their common property resources. This paper also analyze the shift of local wisdom’s role in maintaining balance and harmony between the communities and their surrounding environment, and challenges to the existence of local wisdom associated with population pressures, modernization and development activities with less attention to the preservation of water resources and environment.